2018
DOI: 10.17306/j.afs.0599
|View full text |Cite
|
Sign up to set email alerts
|

Design of a solar dryer for small-farm level use and studying fig quality

Abstract: Background. In the mountain areas of south-east Morocco, farmers are engaged in the solar drying of figs using traditional processes. However, this practice leads to losses in quality. This study aims to improve this drying method by designing and studying the performance of a natural convection solar dryer and the quality of fresh and dried figs. Materials and methods. An indirect solar dryer was designed and its performance was studied. The TSS content, moisture, firmness and morphological parameters of fres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Many studies show that the phenolic content is affected by the drying method (Lachowicz et al, 2019;Liu et al, 2020;Tan et al, 2021;Yap et al, 2020). This was illustrated also by Noutfia et al, (Noutfia et al, 2018;Noutfia et al, 2021) in his studies about fig drying, where the solar method has shown a good quality preservation.…”
Section: Discussionmentioning
confidence: 78%
“…Many studies show that the phenolic content is affected by the drying method (Lachowicz et al, 2019;Liu et al, 2020;Tan et al, 2021;Yap et al, 2020). This was illustrated also by Noutfia et al, (Noutfia et al, 2018;Noutfia et al, 2021) in his studies about fig drying, where the solar method has shown a good quality preservation.…”
Section: Discussionmentioning
confidence: 78%
“…Emerging nations are severely facing the crisis as a substantial part of consumable foodstuff is lost due to mutilation by pests and careless handling (Jain et al, 2019; Prakash et al, 2016). Post‐harvest drying is a crucial food processing activity (Noutfia et al, 2018). Excess moisture is removed from food grain using drying process, which helps to preserve the food grains (Sharma et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Open sun drying is dependent on weather and has other disadvantages like deterioration of food due to the development of microorganisms, birds, animals, insects etc. Solar dryers help to solve these problems and are more efficient, uniform, and economical (Noutfia et al, 2018, 2021; Sharma et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the development of energy‐efficient methods is essential to solving this problem (Castillo‐Téllez et al, 2020). Accordingly, solar drying has largely developed in arid and semiarid areas with optimal climatic conditions (Noutfia et al, 2018). As a result, it has become one of the most attractive and promising solar heat applications for industrial processes as an alternative.…”
Section: Introductionmentioning
confidence: 99%